Smallholders and land tenure in Ghana: Aligning context, empirics, and policy - Lambrecht, Isabel B.; Asare, Sarah (International Food Policy Research Institute, 2015)
For decades, policymakers and development practitioners have debated benefits and threats of property rights formalization and private versus customary tenure systems. This paper provides insights into the challenges in understanding and empirically analyzing the relationship between tenure systems and agricultural investment, and formulates policy advice that can support land tenure interventions. We focus on Ghana, based on extensive qualitative fieldwork and a review of empirical research and policy documents. Comparing research findings is challenging due to the use of different indicators, the varying contexts, and the diversity of investments. The interaction between land rights and investment make establishing causality extremely difficult. Setting policy priorities and strategies requires more and better insights into the diverse responses of different stakeholders and the tenure and cropping systems involved.